KESIAPAN PEGAWAI DALAM MENGHADAPI PERUBAHAN ORGANISASI: STUDI KASUS PADA TRANSFORMASI PTNBH DI UNIVERSITAS TERBUKA - Irmawaty Irmawaty; Rini Febrianti; Yanti Hermawati; Deni Surapto; Nenah Sunarsih (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The success of a university in facing future challenges is highly dependent on the form of management applied. Effective management will be able to bring an organization to shine in this era of globalization. Conversely, ineffective management will make an organization helpless in facing global competition. The transformation of the organization from a State University (PTN) to a State University with Legal Entity (PTN BH) is an initial solution in responding to global trends and to carry out the function of quality higher education that is relevant to the needs of the nation and the development of universal science. This study aims to analyze employee readiness in facing organizational change, especially in the context of the transformation from a Public Service Agency University (PTN-BLU) to a State University with Legal Entity (PTN-BH) at Universitas Terbuka. This study uses a quantitative research method with SEM analysis to examine the relationship between organizational commitment, compensation, and job promotion on employee readiness to face change. The research sample consisted of 400 employees of Universitas Terbuka, who were randomly selected to represent the population. The results of the study indicate that organizational commitment, compensation, and job promotion have a positive and significant influence on employee readiness to face organizational change. These findings contribute to the development of human resource management theory and practice, particularly in the context of organizational change in higher education